2018
DOI: 10.1002/jcp.27154
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a five‐gene signature with prognostic value in colorectal cancer

Abstract: Colorectal cancer (CRC) ranks as one of the most commonly diagnosed malignancies worldwide. Although mortality rates have been decreasing, the prognosis of CRC patients is still highly dependent on the individual. Therefore, identifying and understanding novel biomarkers for CRC prognosis remains crucial. The gene expression profiles of five-gene expression omnibus (GEO) data sets of CRC were first downloaded. A total of 352 consistent differentially expressed genes (DEGs) were identified for CRC and paired wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…In terms of predicting tumor-related prognosis, the accuracy of statistical models and the reduction in interference are superior to single genes or markers [ 17 ]. As high-throughput sequencing technology has developed and databases are increasingly developed, big data can be used to explore statistical models for prediction of tumor prognosis [ 5 ]. Expression data from a large number of genes in each sample can be conveniently processed using big data analysis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of predicting tumor-related prognosis, the accuracy of statistical models and the reduction in interference are superior to single genes or markers [ 17 ]. As high-throughput sequencing technology has developed and databases are increasingly developed, big data can be used to explore statistical models for prediction of tumor prognosis [ 5 ]. Expression data from a large number of genes in each sample can be conveniently processed using big data analysis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing numbers of institutions have adopted multiple genes to build predictive models for disease diagnosis. With the development of high-throughput sequencing technology, an increasing network of public databases have been established whose genetic and clinical data can be exploited to build a prognostic model of related diseases [5].…”
Section: Introductionmentioning
confidence: 99%
“…Further research on these genes is required. It should be noted that SCG2 and PCOLCE2 have been predicted to be associated with the prognosis of CRC, but in-depth investigation on these two genes in CRC is rarely reported [ 42 , 43 ]. It is necessary to explore their roles in tumors, especially in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Solute carrier family 12 member 5 (SLC12A5) contributes to disease progression and metastasis, and is an independent prognostic factor in CRC [19]. Additionally, the prognostic value of the gene signature for predicting prognosis of patients with CRC has been reported [17,18]. However, in advanced CRC, the predictive value of the gene signature is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that single gene expression may have the potential value for predicting prognosis of patients with CRC. Some recent studies have reported the prognostic significance of the gene signature for predicting prognosis of CRC [17,18]. Unfortunately, these recent studies have some limitations, such as relatively small study population, lack of further validation cohort, or analysis of only one or a few genes.…”
Section: Introductionmentioning
confidence: 99%